Statics of granular media - Sokolovskii, V. V. (Vadim Vasilevich), 1912-1978 (Pergamon Press, 1965)
Statics of Granular Media focuses on the theory of limiting equilibrium of a granular medium. The book first discusses the limiting of equilibrium of a granular medium, including limiting conditions, limiting equilibrium of foundations, and limiting plane equilibrium of a granular medium. The text also focuses on the stability of foundations and slopes. Topics include normal restraining pressure on foundations; normal failure pressure on foundations; stability of slopes; and shape of curvilinear curves. The selection also highlights pressure of a fill on retaining walls, including active and p.